Determinants of Executive Compensation in China: The Role and Effect of Corporate Governance and Firm Performance ——Empirical Evidence from Listed Manufacturing Firms - He, Yutong (2020)
In response to public outrage over the executive pay scandals, this paper examines the role and effect of firm performance and corporate governance (CG) on executive compensation in China based on the optimal contract theory and the managerial power theory, contributing to the empirical research on compensation in developing countries. The sample in this research includes 1078 listed manufacturing firms whose executive compensation, performance and corporate governance data from 2015 to 2018 are collected through the CSMAR and CCER databases. On top of that, quantitative analysis is employed to analyze this panel data. By conducting two-way fixed-effect regression models, this research finds the positive connections between firm performance and executive cash compensation, among which the pay-for-market-performance sensitivity is limited and generally lower than the pay-for-operation-performance sensitivity. However, it is also found that CEOs of non-state-owned enterprises (non-SOEs) might increase their pay and decouple the positive connection between executive pay and operation performance when they concurrently serve as the chairman of the board of directors. Moreover, little evidence is found to support the direct and moderating effect of the board independence, presence of compensation committee and the ownership concentration. It indicates that the quality and monitoring role of large shareholders and the board might be overestimated. Therefore, in the future policymaking process, it is necessary to find a way to truly enhance the monitoring role and to increase the bargaining power of large shareholders and the board regarding the design and implementation of optimal executive compensation contracts.